Bureaucratic Reform: A Case Study in Secretariat General of the Ministry of Education and Culture - Muhammad Qudrat Wisnu Aji (Program Pascasarjana Universitas Negeri Makassar, 2019)
Bureaucratic reforms are remedial steps to government tasks and public services, building good governance. The scope of bureaucratic reforms involves not only processes and procedures, but also changes in organizational structure and mindset and behavior of the implementers. The aim of the study is to evaluate the implementation of bureaucratic reform policies carried out by the Secretariat General of the Ministry of Education and Culture. The purposive survey method is used in this study. 80 Echelon III and IV officials in the bureaus within the Secretariat General of the Ministry of Education and Culture participated in this study. The questionnaire was used as an instrument to collect the data in this study. There are three dimensions of bureaucratic reforms examined, namely the basis of reform, the agent of reform and the bureaucratic environment. It was found that bureaucratic reforms significantly influence organizational performance at the Secretariat General of the Ministry of Education and Culture. Bureaucratic reforms are characterized by a good basis of reforms, a strengthening of Human Resources as an agent of bureaucratic reforms and a conducive environment to support the success of bureaucratic reforms to be achieved by the Ministry of Education and Culture.